Advances in Biomaterials for the Prevention and Disruption of Candida Biofilms - Vera-González, Noel; Shukla, Anita (Frontiers in Microbiology, 2020)
Candida species can readily colonize a multitude of indwelling devices, leading to biofilm formation. These three-dimensional, surface-associated Candida communities employ a multitude of sophisticated mechanisms to evade treatment, leading to persistent and recurrent infections with high mortality rates. Further complicating matters, the current arsenal of antifungal therapeutics that are effective against biofilms is extremely limited. Antifungal biomaterials are gaining interest as an effective strategy for combating Candida biofilm infections. In this review, we explore biomaterials developed to prevent Candida biofilm formation and those that treat existing biofilms. Surface functionalization of devices employing clinically utilized antifungals, other antifungal molecules, and antifungal polymers has been extremely effective at preventing fungi attachment, which is the first step of biofilm formation. Several mechanisms can lead to this attachment inhibition, including contact killing and release-based killing of surrounding planktonic cells. Eliminating mature biofilms is arguably much more difficult than prevention. Nanoparticles have shown the most promise in disrupting existing biofilms, with the potential to penetrate the dense fungal biofilm matrix and locally target fungal cells. We will describe recent advances in both surface functionalization and nanoparticle therapeutics for the treatment of Candida biofilms.